Permeable concrete design for heavy metal absorption in sustainable roads - Silva-Juarez, Juan F.; Chavez-Alegria, Omar; Gaxiola-Camacho, J. Ramon; Millan-Almaraz, Jesus R. (Tecnología y ciencias del agua, 2021)
Nowadays, there is a great amount of heavy metals on highways and parking lots. For example, some of such heavy metals are generated mainly by factors as fuel and lubricants leakages, vehicles rust, and carbon emissions. Because of this and some other factors, water pollution occurs due to superficial slurring. In this paper, the application of natural basaltic rocks as an additive for permeable concrete mixtures is presented. During this process, the batch adsorption method is used to determine the effectiveness of the proposed material in removing arsenic (As), zinc (Zn), and cadmium (Cd) concentrations that are typically found in low transit highways and other hydraulic infrastructure. The adsorption test was carried out by immersing 50 mm x 100 mm permeable concrete cylinders in 1-L beakers for 96 h using standard As, Zn, and Cd reagents with 10, 30, 50, and 90 mg/l concentrations, respectively. Results demonstrated that the retention efficiencies were decreased when As and Zn concentrations were increased. However, Cd presented better elimination levels at 90 mg/l concentration where results determined a Cd elimination up to 89 %, 98 % for As, and 75 % for Zn. Finally, based on the results, it is proposed a new methodology for the classification and characterization of basaltic rocks, such a methodology represents a novel process to design permeable concrete material using X-ray fluorescence spectrometry as the base to determine heavy metal absorption on concrete materials. The presented approach will contribute to the improvement of environmental conditions before water treatment processes.